Shape stabilization and laser triggered shape transformation of magnetic particle functionalized liquid metal motors; Colloid and Interface Science Communications; Vol. 47 - Wang Lin; Rutkowski S. Sven; Si Tieyan; Khashem (Mokhamed) T. Takhid; Guo Bin; Xu Jie; Kozelskaya A. I. Anna Ivanovna; Tverdokhlebov S. I. Sergei Ivanovich; Frueh J. С. Johannes Christoph (2022, 2022)
Title screen